An Operational Mechanism for Prosumers to Participate in Real-Time Demand Response - Tan, Zhukui; Liu, Bin; Wu, Yufeng; Zhang, Junwei; Tang, Saiqiu; Xu, Yutao (2022 9th International Forum on Electrical Engineering and Automation (IFEEA), 2022)
As the integrator of prosumers' resources, prosumer aggregator realizes its own economic optimization through multiple interactions with the interest demands of different prosumers at the lower level. In view of the above interaction process, an operational mechanism for prosumers to participate in real-time demand response is proposed based on the master-slave game, in which aggregators aim to maximize its economic benefits and prosumers aim to minimize the cost of electricity consumption. the upper aggregator optimizes the electricity price information according to the power demand / supply information reported by the lower level; The lower level prosumers adjust the internal resource operation plan according to the electricity price information released by the upper level, and modify the overall power demand / supply information. In addition, the improved grey wolf optimization algorithm based on a nonlinear adjustment of the convergence factor (IGWO-NL) is used to solve the Nash equilibrium of the game model. Simulation results show that the proposed model can effectively reduce the peak valley difference of the overall load while optimizing the economy of each subject.